Hemodynamic Simulation Approach to Understanding Blood Flow Dynamics in Stenotic Arteries - Aman Kumar,; Sapna Ratan Shah, (International Journal of Scientific Research in Science and Technology, 2024)
Stenosis, the narrowing of arteries, significantly alters blood flow dynamics and is a major contributor to cardiovascular diseases such as heart attacks and strokes. Understanding the hemodynamic behavior of blood flow through stenotic arteries is crucial for developing effective treatments and interventions. This study presents a hemodynamic simulation approach to explore the effects of varying degrees of stenosis on blood flow characteristics, including velocity distribution, shear stress, and pressure gradient. Simulations were conducted for stenosis degrees ranging from 10% to 80%, with results demonstrating a clear relationship between stenosis severity and changes in blood flow dynamics. As stenosis increased, the velocity of blood flow escalated, reflecting the body's compensatory mechanisms to overcome increased resistance. Shear stress on arterial walls also heightened, particularly at the stenotic entry and exit points, which could contribute to endothelial injury and plaque formation. Additionally, the pressure gradient across the stenotic section increased with the degree of stenosis, indicating a higher energy requirement for blood circulation. These findings provide critical insights into the hemodynamic implications of arterial stenosis and underscore the importance of early detection and intervention in preventing severe cardiovascular events.
Keywords: blood flow dynamics; Hemodynamic simulation; shear stress; stenotic arteries; velocity distribution; pressure gradient; arterial stenosis; cardiovascular modeling; bioinspired approach; computational fluid dynamics; blood flow resistance; stenosis severity; vascular health; flow patterns; cardiovascular risk